Analysis of Learning Styles Based on Indonesian Language Learning Outcomes in Elementary School Students - Purbayani, Rini; Nugraha, Anggi Purwa; Ali, Nabila Nurhaliza (Journal Corner of Education, Linguistics, and Literature, 2024)
Understanding students' learning styles is a key factor in effective learning, as it helps teachers optimize the teaching and learning process and improve student success. This study aims to examine the relationship between students' learning styles and learning outcomes in the Indonesian language subject. The research uses a survey method with a sample of 46 fifth-grade elementary school students using saturated sampling techniques. The results indicate that the majority of students have a kinesthetic learning style (43.5%), followed by visual learning styles (30.4%) and auditory styles (26.1%). The learning outcomes of visual learners are higher compared to the others, with an average score of 84.3 in the good category, while auditory learners perform better than kinesthetic learners but lower than visual learners, with an average score of 81.4 in the fair category, whereas kinesthetic learners have lower results compared to the others, with an average score of 79.5 in the fair category. This suggests that a teaching process that does not consider the diversity of learning styles can negatively impact students' learning outcomes. Therefore, teachers need to pay attention to students' learning styles to enhance learning effectiveness so that students' learning outcomes can be optimal.